Carnap's Ideal of Explication and Naturalism
XII, 263 p.
Keywords: The book consists of a series of chapters on Carnap's ideal of explication as an alternative to the naturalistic conceptions of science, setting it in its historical context, discussing specific cases of explications, and enriching the on-going debate on conceptual engineering and naturalism in analytic philosophy.